Corporate Liability for Air Pollution Based on Strict Liability in Indonesia: A Study of the Absence of Standards for Measuring Non-Material Damages - Faliani Zaliaokta; Distya Rahma Fauzia; Livia Fajarisalfa; Siti Maharani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Air pollution constitutes a significant environmental problem with far-reaching impacts on public health, quality of life, and ecosystem sustainability, particularly in urban areas and industrial zones in Indonesia. Although the national environmental legal framework has adopted the principle of strict liability through Law Number 32 of 2009 on Environmental Protection and Management, its implementation in air pollution cases continues to face substantial challenges, especially with regard to the proof and assessment of non-material damages. Non-material damages such as disturbances to living comfort, deterioration of environmental quality, psychological stress, and health-related anxiety are intangible in nature and lack clear measurement standards, resulting in their frequent exclusion or inadequate consideration in environmental civil litigation. This study aims to analyze the legal basis for the application of the strict liability principle to air pollution cases in Indonesia, identify relevant forms of non-material damage, and examine the implications of the absence of standardized methods for assessing such damages on legal certainty and the effectiveness of corporate liability enforcement. The research employs a normative legal research method with a library-based approach, incorporating statutory, conceptual, and case approaches. Legal materials are analyzed qualitatively using a descriptive-analytical method, drawing upon legislation, court decisions, and scholarly literature on environmental law and environmental damage valuation. The findings indicate that the absence of standardized criteria for assessing non-material damages leads to evidentiary difficulties, inconsistent court decisions, and a weakened deterrent effect on polluting corporations, thereby preventing the full realization of victims’ rights to effective remedies. This study underscores the urgency of developing an integrated national technical guideline for the assessment of non-material environmental damages based on scientifically grounded valuation methods, as well as the need for cross-institutional policy harmonization to strengthen legal certainty, access to justice for affected communities, and corporate accountability in controlling air pollution.